Pengaruh Tata Kelola Perusahaan terhadap Kinerja Keuangan Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Athaya Fatin; Zulkifli Umar; Budi Safatul Anam (AKUNTANSI 45, 2025)
This study analyzes the effect of corporate governance on the financial performance of banks on the IDX for the period 2021-2023, with the independent variables of the board of directors, institutional ownership, and audit committee, as well as financial performance as measured by ROA. Using a quantitative approach with panel data regression, this study took a sample of 24 banking companies through purposive sampling based on the availability of annual reports and the implementation of good governance. Data was obtained from the company’s annual report downloaded from the IDX. The results showed that the board of directors and institutional ownership had a positive and significant effect on banking financial performance, while the audit committee had no significant effect. Simultaneously, corporate governance consisting of the board of directors, institutional ownership, and audit committee has a significant effect on financial performance. The implication is that strengthening governance, especially through the effectiveness of the board of directors and institutional ownership, can improve the financial performance of banks and be a consideration for management, investors, and regulators in increasing transparency and effectiveness of governance in the banking sector.